Liquid crystal alignment agent, liquid crystal alignment film, and liquid crystal display element
By using a liquid crystal aligning agent made of a polyimide precursor of a specific structure and an imidized polymer, the afterimide image problem caused by insufficient anisotropy of the liquid crystal aligning film obtained by the photo-oriented method is solved, and the effects of high liquid crystal aligning properties and low afterimage are achieved.
Patent Information
- Application Number
- CN201980072451.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-11-06
- Filing Date
- 2019-11-05
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2039-11-05
AI Technical Summary
The liquid crystal alignment film obtained by the photo-oriented method lacks anisotropy in the orientation direction, resulting in a problem of afterimage after AC drive.
A liquid crystal alignment agent is used, which contains a polyimide precursor of a specific structure and an imidized polymer thereof, and a liquid crystal alignment film composed of these materials is used to improve the orientation of the liquid crystal.
By using the liquid crystal aligning agent, a film with high liquid crystal aligning can be obtained, and the generation of afterimage after AC drive can be effectively suppressed.
Smart Images

Figure CN112969959B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a liquid crystal aligning agent used for producing a liquid crystal display element, a liquid crystal aligning film obtained from the liquid crystal aligning agent, and a liquid crystal display element having the liquid crystal aligning film. Background Art
[0002] As a frictionless orientation treatment method, the photo-orientation method is also a simple manufacturing process in industry. In particular, in the liquid crystal display element of the plane switching (IPS, In-Plane-Switching) driving mode and the boundary electric field switching (FFS, Flinge fieldSwitching) driving mode, by using the liquid crystal orientation film obtained by the above-mentioned photo-orientation method, compared with the liquid crystal orientation film obtained by the friction treatment method, it can be expected that the contrast and viewing angle characteristics of the liquid crystal display element will be improved (Patent Document 1). As a result, the performance of the liquid crystal display element can be improved, and it has attracted attention as a promising liquid crystal orientation treatment method.
[0003] However, the liquid crystal alignment film obtained by the photo-alignment method has a problem that the polymer film has a small anisotropy in the orientation direction compared to the liquid crystal alignment film obtained by rubbing. If the anisotropy is small, sufficient liquid crystal orientation cannot be obtained, and when a liquid crystal display element is formed, there are problems such as afterimages (Non-Patent Document 1).
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Laid-Open No. 9-297313
[0007] Non-patent literature
[0008] Non-patent document 1: "Liquid crystal photo-alignment film (liquid crystal photo-alignment film)" Functional materials (functional materials), Vol.17 (1997), No.11, p.13-22 Summary of the invention
[0009] Problem that the invention aims to solve
[0010] An object of the present invention is to suppress the generation of an afterimage after AC driving due to insufficient anisotropy of a liquid crystal alignment film obtained by a photo-alignment method in an alignment direction.
[0011] Solutions for solving problems
[0012] The present inventors have conducted intensive studies to solve the above problems and have completed the present invention. That is, the present invention is as follows.
[0013] A liquid crystal aligning agent comprising at least one polymer selected from the group consisting of a polyimide precursor having a structure represented by the following formula (1) in its main chain and an imidized polymer of the polyimide precursor.
[0014] -B1-R1-A-R2-B2-(1)
[0015] In the formula, R1 and R2 are each independently a single bond, -O-, -S-, -NR 12 -, ester bond, amide bond, thioester bond, urea bond, carbonate bond, or carbamate bond. 12 is a hydrogen atom or a methyl group. A is an alkylene group having 1 or 2 carbon atoms. B1 and B2 have the same structure and are divalent organic groups selected from the following structures.
[0016]
[0017] In the formula, R4 is an alkylene group having 1 to 5 carbon atoms. R5 is a hydrogen atom, a methyl group, a hydroxyl group or a methoxy group.
[0018] Effects of the Invention
[0019] By using the liquid crystal aligning agent of this invention, it has high liquid-crystal orientation, and can obtain the liquid crystal aligning film which can suppress the generation|occurrence|production of AC afterimage.
[0020] Although it is not necessarily clear why the above-mentioned effect is obtained by using the liquid crystal aligning agent of the present invention, it is presumed that this is because the chemical structure of the diamine which is a raw material of the polymer constituting the liquid crystal alignment material is rigid and has a symmetrical structure. DETAILED DESCRIPTION
[0021] <Specific structure>
[0022] The specific structure (hereinafter also referred to as a specific structure) represented by the above formula (1) is contained in the main chain of the polymer constituting the liquid crystal aligning agent of the present invention.
[0023] -B1-R1-A-R2-B2- (1)
[0024] In the above formula (1), R1 and R2 are each independently a single bond, -O-, -S-, -NR 12 -, ester bond, amide bond, thioester bond, urea bond, carbonate bond, or carbamate bond. 12 is a hydrogen atom or a methyl group. A is an alkylene group having 1 or 2 carbon atoms. B1 and B2 have the same structure and are divalent organic groups selected from the following structures. When B1 and B2 have the same structure, a liquid crystal alignment film having high liquid crystal alignment can be obtained.
[0025]
[0026] In the above formula, R4 is an alkylene group having 1 to 5 carbon atoms. R5 is a hydrogen atom, a methyl group, a hydroxyl group or a methoxy group.
[0027] In the above formula (1), R1 and R2 are preferably a single bond, -O-, -S-, or -NR from the viewpoint of liquid crystal orientation. 12 -, ester bond or amide bond, particularly preferably -O-. 12 From the viewpoint of liquid crystal orientation, a hydrogen atom or a methyl group is preferred. Moreover, from the viewpoint of liquid crystal orientation, A is preferably an alkylene group having 2 carbon chains.
[0028] B1 and B2 are preferably biphenylene groups from the viewpoint of liquid crystal orientation.
[0029] In the above formula, R4 is preferably an alkylene group having 1 to 3 carbon atoms from the viewpoint of liquid crystal orientation. R5 is preferably a hydrogen atom or a methyl group from the viewpoint of liquid crystal orientation.
[0030] The above-mentioned specific structure is preferably contained in the diamine as the raw material of the polyimide precursor. As specific examples of the diamine having the above-mentioned specific structure, the following diamines can be listed, but they are not limited to them. The polyimide precursor is preferably obtained by polymerization reaction of a diamine component containing at least one diamine selected from the following diamines and a tetracarboxylic acid component.
[0031]
[0032] (R5 has the same definition as above.)
[0033]
[0034] In the above formula, R5 and R 12 The definitions including respective preferred examples are the same as above.
[0035] The diamine having the above-mentioned specific structure is preferably a diamine in which amino groups are bonded to both ends of the above-mentioned specific structure. Among them, the following diamines are preferred from the viewpoint of alignment and reduction of bright spots when forming a liquid crystal display element.
[0036]
[0037] In the above formula, R1, R2, and A are as described above including their respective preferred examples. As the diamine having the above specific structure, the following diamines are preferred.
[0038]
[0039] <Polymer>
[0040] The polyimide precursor constituting the liquid crystal aligning agent of the present invention contains a structural unit of the following formula (2).
[0041]
[0042] X1 is at least one selected from the group consisting of structures represented by the following formulae (X1-1) and (X1-2).
[0043] Among these, from the viewpoint of liquid crystal orientation, the following formula (X1-2) is preferred.
[0044]
[0045] Y1 is a divalent organic group represented by formula (1).
[0046] R3 is a hydrogen atom or an alkyl group having 1 to 5 carbon atoms. Specific examples thereof include methyl, ethyl, propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, etc. From the viewpoint of the ease of imidization by heating, R3 is preferably a hydrogen atom or a methyl group.
[0047] Z1 and Z2 are each independently a hydrogen atom, or an alkyl group having 1 to 10 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, or an alkynyl group having 2 to 10 carbon atoms, which may have a substituent. Specific examples of alkyl groups include methyl, ethyl, propyl, butyl, tert-butyl, hexyl, octyl, decyl, cyclopentyl, cyclohexyl, and bicyclohexyl. As alkenyl groups, alkenyl groups in which one or more CH2-CH2 structures present in the above-mentioned alkyl groups are replaced with CH=CH structures can be listed. Specifically, vinyl, allyl, 1-propenyl, isopropenyl, 2-butenyl, 1,3-butadienyl, 2-pentenyl, 2-hexenyl, cyclopropenyl, cyclopentenyl, and cyclohexenyl can be listed. As alkynyl groups, alkynyl groups in which one or more CH2-CH2 structures present in the above-mentioned alkyl groups are replaced with C≡C structures can be listed. Specifically, ethynyl, 1-propynyl, and 2-propynyl can be listed.
[0048] The above-mentioned alkyl, alkenyl and alkynyl groups may have substituents, and may further form a ring structure through the substituents. It should be noted that forming a ring structure through substituents means that substituents are bonded to each other or to a part of the parent skeleton to form a ring structure.
[0049] Examples of the substituent include a halogen group, a hydroxyl group, a mercapto group, a nitro group, an aryl group, an organic oxy group, an organic thio group, an organic silyl group, an acyl group, an ester group, a thioester group, a phosphate group, an amide group, an alkyl group, an alkenyl group, and an alkynyl group.
[0050] Examples of the halogen group include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom.
[0051] Examples of the aryl group include a phenyl group. The aryl group may be further substituted with the other substituents described above.
[0052] As the organic oxy group, the structure represented by -OR can be shown. The R can be the same or different, and the aforementioned alkyl, alkenyl, alkynyl, aryl, etc. can be exemplified. The aforementioned substituent can be further substituted by these R. As specific examples, methoxy, ethoxy, propoxy, butoxy, pentyloxy, hexyloxy, heptyloxy, octyloxy, etc. can be listed.
[0053] As an organic thio group, a structure represented by -SR can be shown. As this R, the aforementioned alkyl, alkenyl, alkynyl, aryl, etc. can be exemplified. The aforementioned substituents can be further substituted with these R. As specific examples, methylthio, ethylthio, propylthio, butylthio, pentylthio, hexylthio, heptylthio, octylthio, etc. can be listed.
[0054] As an organosilyl group, a structure represented by -Si-(R)3 can be shown. The Rs may be the same or different, and examples thereof include the aforementioned alkyl, alkenyl, alkynyl, aryl, etc. The aforementioned substituents may be further substituted with these Rs. As specific examples, trimethylsilyl, triethylsilyl, tripropylsilyl, tributylsilyl, tripentylsilyl, trihexylsilyl, pentyldimethylsilyl, hexyldimethylsilyl, etc. can be cited.
[0055] As the acyl group, a structure represented by -C(O)-R can be shown. As the R, the aforementioned alkyl, alkenyl, aryl, etc. can be exemplified. The aforementioned substituents may further substitute on these R. As specific examples, formyl, acetyl, propionyl, butyryl, isobutyryl, valeryl, isovaleryl, benzoyl, etc. can be listed.
[0056] As the ester group, a structure represented by -C(O)OR or -OC(O)-R can be shown. Examples of R include the above-mentioned alkyl group, alkenyl group, alkynyl group, aryl group, etc. These R groups may be further substituted by the above-mentioned substituents.
[0057] As the thioester group, a structure represented by -C(S)OR or -OC(S)-R can be shown. Examples of R include the above-mentioned alkyl group, alkenyl group, alkynyl group, aryl group, etc. These R groups may be further substituted by the above-mentioned substituents.
[0058] As the phosphate group, a structure represented by -OP(O)-(OR)2 can be shown. The R's may be the same or different, and examples thereof include the aforementioned alkyl, alkenyl, alkynyl, aryl, etc. The aforementioned substituents may further substitute on these R's.
[0059] As an amide group, a structure represented by -C(O)NH2, -C(O)NHR, -NHC(O)R, -C(O)N(R)2, or -NRC(O)R can be shown. The Rs may be the same or different, and examples thereof include the aforementioned alkyl, alkenyl, alkynyl, aryl, etc. The aforementioned substituents may further substitute on these Rs.
[0060] Examples of the aryl group include the same examples as those for the above-mentioned aryl group. The above-mentioned other substituent may further substitute on the aryl group.
[0061] Examples of the alkyl group include the same examples as those mentioned above. The alkyl group may be further substituted with the other substituents mentioned above.
[0062] Examples of the alkenyl group include the same examples as those for the alkenyl group described above. The alkenyl group may be further substituted with the other substituents described above.
[0063] Examples of the alkynyl group include the same examples as those for the above-mentioned alkynyl group. The above-mentioned other substituent may further substitute on the alkynyl group.
[0064] Generally, when a bulky structure is introduced, the reactivity of the amino group and the liquid crystal orientation may be reduced. Therefore, Z1 and Z2 are more preferably a hydrogen atom or an alkyl group having 1 to 5 carbon atoms which may have a substituent, and particularly preferably a hydrogen atom, a methyl group or an ethyl group.
[0065] The content of the structural unit represented by the above formula (2) is preferably 20 to 100 mol % based on all structural units, and particularly preferably 30 to 100 mol % from the viewpoint of liquid crystal orientation.
[0066] <Other structural units>
[0067] When the polymer constituting the liquid crystal aligning agent of the present invention contains a structural unit other than the structural unit of the above formula (2), the structural unit is represented by the following formula (3).
[0068]
[0069] R3, Z1 and Z2 are as defined in the above formula (2).
[0070] X2 is a tetravalent organic group, and Y2 is a divalent organic group.
[0071] X2 is a tetravalent organic group derived from a tetracarboxylic acid derivative, and its structure is not particularly limited. In the polyimide precursor, two or more types of X2 may be mixed. Specific examples of X2 include the following structures of formulae (X-1) to (X-44).
[0072]
[0073] In the above formula (X-1), R8 to R 11 Each of R8 to R1 is independently a hydrogen atom, a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkenyl group having 2 to 6 carbon atoms, an alkynyl group having 2 to 6 carbon atoms, or a phenyl group. 11 In the case of a bulky structure, the liquid crystal orientation may decrease, and therefore a hydrogen atom, a methyl group or an ethyl group is more preferred, and a hydrogen atom or a methyl group is particularly preferred.
[0074] In formula (3), Y2 is a divalent organic group derived from diamine, and its structure is not particularly limited. Specific examples of the structure of Y2 include the following formulas (Y-1) to (Y-118).
[0075]
[0076]
[0077]
[0078]
[0079] (In formula (Y-109), m and n are each independently an integer of 1 to 11, m+n is an integer of 2 to 12, in formula (Y-114), h is an integer of 1 to 3, and in formulas (Y-111) and (Y-117), j is an integer of 0 to 3.)
[0080] The polyimide precursor used in the present invention is obtained by reaction between a diamine component and a tetracarboxylic acid derivative, and examples thereof include a polyamic acid and a polyamic acid ester.
[0081] <Polyimide precursor (polyamic acid)>
[0082] The polyamic acid which is a polyimide precursor used in the present invention is produced by the following method.
[0083] Specifically, it can be synthesized by reacting tetracarboxylic dianhydride and diamine in the presence of an organic solvent at -20°C to 150°C, preferably 0°C to 50°C, for 30 minutes to 24 hours, preferably 1 to 12 hours.
[0084] The reaction of the diamine component and the tetracarboxylic acid component is usually carried out in an organic solvent. As the organic solvent used at this time, it is not particularly limited if it is an organic solvent in which the generated polyimide precursor is dissolved. Specific examples of the organic solvent used in the reaction are listed below, but are not limited to these examples. For example, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, γ-butyrolactone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide or 1,3-dimethyl-imidazolidinone can be listed.
[0085] When the solubility of the polyimide precursor is high, methyl ethyl ketone, cyclohexanone, cyclopentanone, 4-hydroxy-4-methyl-2-pentanone, or an organic solvent represented by the following formula [D-1] to [D-3] can be used.
[0086]
[0087] In formula [D-1], D 1 represents an alkyl group having 1 to 3 carbon atoms, wherein in the formula [D-2], D 2 represents an alkyl group having 1 to 3 carbon atoms, wherein D 3 It represents an alkyl group having 1 to 4 carbon atoms.
[0088] These solvents can be used alone or in combination. Furthermore, even if it is a solvent that does not dissolve the polyimide precursor, it can be mixed in the aforementioned solvent and used within the range that the generated polyimide precursor will not precipitate. In addition, the moisture in the solvent becomes the cause of hindering the polymerization reaction and then hydrolyzing the generated polyimide precursor, so the solvent is preferably a dehydrated solvent.
[0089] The concentration of the polyamic acid polymer in the reaction system is preferably 1 to 30% by mass, more preferably 5 to 20% by mass, from the viewpoint of preventing precipitation of the polymer and easily obtaining a high molecular weight product.
[0090] For the polyamic acid obtained as described above, by fully stirring the reaction solution while injecting it into a poor solvent, the polymer can be precipitated and recovered. In addition, precipitation is performed several times, and after washing with a poor solvent, normal temperature or heating drying is performed, thereby a powder of purified polyamic acid can be obtained. The poor solvent is not particularly limited, and water, methanol, ethanol, hexane, butyl cellosolve, acetone, toluene, etc. can be listed.
[0091] <Polyimide precursor (polyamic acid ester)>
[0092] The polyamic acid ester which is a polyimide precursor used for this invention can be manufactured by the manufacturing method of (1), (2) or (3) shown below.
[0093] (1) When made from polyamic acid
[0094] Polyamic acid ester can be produced by esterifying the polyamic acid produced as described above. Specifically, it can be produced by reacting a polyamic acid with an esterifying agent in the presence of an organic solvent at -20°C to 150°C, preferably 0°C to 50°C for 30 minutes to 24 hours, preferably 1 to 4 hours.
[0095] The esterifying agent is preferably an esterifying agent that can be easily removed by purification, and examples thereof include N,N-dimethylformamide dimethyl acetal, N,N-dimethylformamide diethyl acetal, N,N-dimethylformamide dipropyl acetal, N,N-dimethylformamide dineopentyl butyl acetal, N,N-dimethylformamide di-tert-butyl acetal, 1-methyl-3-p-tolyltriazene, 1-ethyl-3-p-tolyltriazene, 1-propyl-3-p-tolyltriazene, 4-(4,6-dimethoxy-1,3,5-triazine-2-yl)-4-methylmorpholinium chloride, etc. The amount of the esterifying agent added is preferably 2 to 6 molar equivalents relative to 1 mol of the repeating unit of the polyamic acid.
[0096] Examples of the organic solvent include N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, γ-butyrolactone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, and 1,3-dimethyl-imidazolidinone. In addition, when the polyimide precursor has high solvent solubility, methyl ethyl ketone, cyclohexanone, cyclopentanone, 4-hydroxy-4-methyl-2-pentanone, or solvents represented by the above formulas [D-1] to [D-3] can be used.
[0097] These solvents can be used alone or in combination. Furthermore, even if it is a solvent that does not dissolve the polyimide precursor, it can be mixed in the aforementioned solvent and used within the range that the generated polyimide precursor will not precipitate. In addition, the moisture in the solvent becomes the cause of hindering the polymerization reaction and then hydrolyzing the generated polyimide precursor, so the solvent is preferably a dehydrated solvent.
[0098] The solvent used in the above reaction is preferably N,N-dimethylformamide, N-methyl-2-pyrrolidone or γ-butyrolactone from the viewpoint of polymer solubility, and these can be used alone or in combination of two or more. The concentration during production is preferably 1 to 30% by mass, more preferably 5 to 20% by mass, from the viewpoint of not easily causing the precipitation of the polymer and easily obtaining a high molecular weight body.
[0099] (2) When produced by reaction of tetracarboxylic acid diester dichloride and diamine
[0100] Polyamic acid ester can be produced from tetracarboxylic acid diester dichloride and diamine.
[0101] Specifically, it can be produced by reacting a tetracarboxylic acid diester dichloride with a diamine in the presence of a base and an organic solvent at -20°C to 150°C, preferably 0°C to 50°C, for 30 minutes to 24 hours, preferably 1 to 4 hours.
[0102] As the base, pyridine, triethylamine, 4-dimethylaminopyridine, etc. can be used, but pyridine is preferred for mild reaction. The amount of the base added is preferably 2 to 4 times the mole of the tetracarboxylic acid diester dichloride from the viewpoint of being an amount that is easily removed and easily obtaining a high molecular weight product.
[0103] For the solvent used in the above reaction, N-methyl-2-pyrrolidone or γ-butyrolactone is preferred from the solubility of monomers and polymers, and they can be used alone or in combination of two or more. For the polymer concentration during manufacture, from the viewpoint of not easily producing the precipitation of the polymer and easily obtaining a high molecular weight body, 1 to 30% by mass is preferred, and 5 to 20% by mass is more preferred. In addition, in order to prevent the hydrolysis of the tetracarboxylic acid diester dichloride, the solvent used in the manufacture of polyamic acid ester is preferably dehydrated as much as possible, preferably in a nitrogen atmosphere to prevent external gas from mixing.
[0104] (3) When produced from tetracarboxylic acid diester and diamine
[0105] Polyamic acid ester can be produced by polycondensation of a tetracarboxylic-acid diester and a diamine.
[0106] Specifically, it can be produced by reacting a tetracarboxylic acid diester with a diamine in the presence of a condensing agent, a base and an organic solvent at 0°C to 150°C, preferably 0°C to 100°C, for 30 minutes to 24 hours, preferably 3 to 15 hours.
[0107] The condensing agent may be triphenylphosphite, dicyclohexylcarbodiimide, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride, N,N'-carbonyldiimidazole, dimethoxy-1,3,5-triazinylmethylmorpholinium, O-(benzotriazol-1-yl)-N,N,N',N'-tetramethyluronium tetrafluoroborate, O-(benzotriazol-1-yl)-N,N,N',N'-tetramethyluronium hexafluorophosphate, (2,3-dihydro-2-thioxo-3-benzoxazolyl)phosphonic acid diphenyl ester, etc. The amount of the condensing agent added is preferably 2 to 3 times the molar amount of the tetracarboxylic acid diester.
[0108] As the base, a tertiary amine such as pyridine or triethylamine can be used. The amount of the base added is preferably 2 to 4 times the molar amount of the diamine component from the viewpoint of being an amount that is easily removed and easily obtaining a high molecular weight product.
[0109] In the above reaction, the reaction can be efficiently carried out by adding a Lewis acid as an additive. The Lewis acid is preferably a lithium halide such as lithium chloride or lithium bromide. The amount of the Lewis acid added is preferably 0 to 1.0 times the mole of the diamine component.
[0110] In order to obtain high molecular weight polyamic acid ester among the manufacturing methods of the said three types of polyamic acid ester, the manufacturing method of said (1) or (2) is especially preferable.
[0111] The solution of polyamic acid ester obtained as described above can be injected into a poor solvent while being fully stirred to precipitate the polymer. After several precipitations, washing with a poor solvent, and drying at room temperature or by heating, a powder of purified polyamic acid ester can be obtained. The poor solvent is not particularly limited, and water, methanol, ethanol, hexane, butyl cellosolve, acetone, toluene, etc. can be listed.
[0112] <Polyimide>
[0113] The polyimide used in the present invention can be produced by imidizing the above-mentioned polyamic acid ester or polyamic acid.
[0114] When polyimide is produced from polyamic acid ester, chemical imidization by adding a basic catalyst to a polyamic acid ester solution or a polyamic acid solution obtained by dissolving polyamic acid ester resin powder in an organic solvent is simple. Chemical imidization is preferred because the imidization reaction is carried out at a relatively low temperature and the molecular weight of the polymer is not easily reduced during the imidization process.
[0115] Chemical imidization can be carried out by stirring the polyamic acid ester to be imidized in an organic solvent in the presence of a basic catalyst. As an organic solvent, the solvent used in the aforementioned polymerization reaction can be used. As a basic catalyst, pyridine, triethylamine, trimethylamine, tributylamine, trioctylamine, etc. can be listed. Among them, triethylamine is preferred because it has sufficient alkalinity for reacting.
[0116] The temperature during the imidization reaction is -20°C to 140°C, preferably 0°C to 100°C, and the reaction time is preferably 1 to 100 hours. The amount of the basic catalyst is 0.5 to 30 mole times of the amic acid ester group, preferably 2 to 20 mole times. The imidization rate of the obtained polymer can be controlled by adjusting the amount of catalyst, temperature, reaction time, etc. Since the added catalyst and the like remain in the solution after the imidization reaction, it is preferred to recover the obtained imidized polymer by the means described below, and redissolve it with an organic solvent to obtain the liquid crystal alignment agent of the present invention.
[0117] When polyimide is produced from polyamic acid, chemical imidization by adding a catalyst to a solution of polyamic acid obtained by the reaction of a diamine component and tetracarboxylic dianhydride is simple. Chemical imidization is preferred because the imidization reaction is carried out at a relatively low temperature and the molecular weight of the polymer is not easily reduced during the imidization process.
[0118] Chemical imidization can be carried out by stirring the polyamic acid to be imidized in an organic solvent in the presence of a basic catalyst and an acid anhydride. As an organic solvent, the solvent used during the aforementioned polymerization reaction can be used. As a basic catalyst, pyridine, triethylamine, trimethylamine, tributylamine, trioctylamine, etc. can be listed. Among them, pyridine is preferred because it has a moderate alkalinity for reacting. In addition, as an acid anhydride, acetic anhydride, trimellitic anhydride, pyromellitic anhydride, etc. can be listed. Among them, acetic anhydride is preferred because purification after the reaction is completed becomes easy.
[0119] The temperature during the imidization reaction is -20°C to 140°C, preferably 0°C to 100°C, and the reaction time can be preferably 1 to 100 hours. The amount of the basic catalyst is 0.5 to 30 times by mole, preferably 2 to 20 times by mole, of the amic acid group, and the amount of the acid anhydride is 1 to 50 times by mole, preferably 3 to 30 times by mole. The imidization rate of the obtained polymer can be controlled by adjusting the amount of catalyst, temperature, reaction time, etc.
[0120] Since the added catalyst etc. remain in the solution after the imidization reaction of polyamic acid ester or polyamic acid, it is preferable to recover the obtained imidized polymer by the means described below, and to redissolve it with an organic solvent to obtain the liquid crystal aligning agent of the present invention.
[0121] The polyimide solution obtained as described above can be poured into a poor solvent while being sufficiently stirred to precipitate a polymer. The precipitation can be repeated several times, and after washing with a poor solvent, the solution is dried at room temperature or by heating to obtain a purified polyimide powder.
[0122] The poor solvent is not particularly limited, and examples thereof include methanol, acetone, hexane, butyl cellosolve, heptane, methyl ethyl ketone, methyl isobutyl ketone, ethanol, toluene, and benzene.
[0123] <Liquid crystal alignment agent>
[0124] The liquid crystal aligning agent of the present invention contains at least one polymer selected from the group consisting of a polyimide precursor having a specific structure in the main chain and an imidized polymer of the polyimide precursor. The molecular weight of the polymer is preferably 2000 to 500000, more preferably 5000 to 300000, and further preferably 10000 to 100000 in terms of weight average molecular weight (Mw). In addition, the number average molecular weight (Mn) is preferably 1000 to 250000, more preferably 2500 to 150000, and further preferably 5000 to 50000.
[0125] The concentration of the polymer in the liquid crystal aligning agent of the present invention can be appropriately changed according to the setting of the thickness of the coating film to be formed, but from the viewpoint of forming a uniform and defect-free coating film, it is preferably 1% by mass or more, and from the viewpoint of the storage stability of the solution, it is preferably 10% by mass or less. The concentration of the polymer is preferably 2 to 7% by mass.
[0126] The organic solvent which dissolves a polymer (hereinafter also referred to as a good solvent) contained in the liquid crystal aligning agent used for this invention will not be specifically limited as long as it is an organic solvent which melt|dissolves a polymer uniformly.
[0127] Examples thereof include N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, dimethyl sulfoxide, γ-butyrolactone, 1,3-dimethyl-imidazolidinone, methyl ethyl ketone, cyclohexanone, cyclopentanone, and 4-hydroxy-4-methyl-2-pentanone. Among them, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, and γ-butyrolactone are preferably used.
[0128] Furthermore, when the solubility of the polymer of the present invention in a solvent is high, it is preferable to use a solvent represented by the above formula [D-1] to formula [D-3].
[0129] It is preferable that content of the good solvent in the liquid crystal aligning agent of this invention is 20-99 mass % of all solvents contained in a liquid crystal aligning agent. Among them, it is preferably 20-90 mass %, and it is more preferably 30-80 mass %.
[0130] The liquid crystal aligning agent of the present invention can use a solvent (also referred to as a poor solvent) that improves the coating properties and surface smoothness of the liquid crystal aligning film when the liquid crystal aligning agent is applied. Specific examples of the poor solvent can be given.
[0131] Examples thereof include ethanol, isopropanol, 1-butanol, 2-butanol, isobutanol, tert-butanol, 1-pentanol, 2-pentanol, 3-pentanol, 2-methyl-1-butanol, isopentanol, tert-pentanol, 3-methyl-2-butanol, neopentyl alcohol, 1-hexanol, 2-methyl-1-pentanol, 2-methyl-2-pentanol, 2-ethyl-1-butanol, 1-heptanol, 2-heptanol, 3-heptanol, 1-octanol, 2-octanol, 2-ethyl-1-hexanol, cyclohexanol, 1-methylcyclohexanol, 2-methylcyclohexanol, 3-methylcyclohexanol, 1,2-ethanediol, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-butylene glycol, 1,3-butylene glycol, 1 ,4-Butanediol, 2,3-Butanediol, 1,5-Pentanediol, 2-Methyl-2,4-pentanediol, 2-Ethyl-1,3-Hexanediol, Dipropyl Ether, Dibutyl Ether, Dihexyl Ether, Dioxane, Ethylene Glycol Dimethyl Ether, Ethylene Glycol Diethyl Ether, Ethylene Glycol Dibutyl Ether, 1,2-Butoxyethane, Diethylene Glycol Dimethyl Ether, Diethylene Glycol Diethyl Ether, Diethylene Glycol Methyl Ether, Diethylene Glycol Dibutyl Ether, 2-Pentanone, 3-Pentanone, 2-Hexanone, 2-Heptanone, 4-Heptanone, 3-Ethoxybutyl Acetate, 1-Methylpentyl Acetate, 2-Ethylbutyl Acetate, 2-Ethylhexyl Acetate, Ethylene Glycol Monoacetate, Ethylene Glycol Diacetate, Propylene carbonate, ethylene carbonate, 2-(methoxymethoxy)ethanol, ethylene glycol monobutyl ether, ethylene glycol monoisoamyl ether, ethylene glycol monohexyl ether, 2-(hexyloxy)ethanol, furfuryl alcohol, diethylene glycol, propylene glycol, propylene glycol monobutyl ether, 1-(butoxyethoxy)propanol, propylene glycol monomethyl ether acetate, dipropylene glycol, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol dimethyl ether, tripropylene glycol monomethyl ether, ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, ethylene glycol monobutyl ether acetate, ethylene glycol monoacetate, ethylene glycol diacetate, diethylene glycol monoethyl ether acetate, diethylene glycol monobutyl ethyl acetate, 2-(2-ethoxyethoxy)ethyl acetate, diethylene glycol acetate, triethylene glycol, triethylene glycol monomethyl ether, triethylene glycol monoethyl ether, methyl lactate, ethyl lactate, methyl acetate, ethyl acetate, n-butyl acetate, propylene glycol monoethyl acetate, methyl pyruvate, ethyl pyruvate, methyl 3-methoxypropionate, methyl ethyl 3-ethoxypropionate, ethyl 3-methoxypropionate, 3-ethoxypropionic acid, 3-methoxypropionic acid, propyl 3-methoxypropionate, butyl 3-methoxypropionate, methyl lactate, ethyl lactate, n-propyl lactate, n-butyl lactate, isoamyl lactate, and the solvents represented by the above formulas [D-1] to [D-3].
[0132] Among them, 1-hexanol, cyclohexanol, 1,2-ethylene glycol, 1,2-propylene glycol, propylene glycol monobutyl ether, ethylene glycol monobutyl ether or dipropylene glycol dimethyl ether is preferred.
[0133] The content of these poor solvents is preferably 1 to 80% by mass of the total solvents contained in the liquid crystal aligning agent, and among these, 10 to 80% by mass is preferred, and 20 to 70% by mass is more preferred.
[0134] The liquid crystal alignment agent of the present invention may further include, in addition to the above, polymers other than the polymer of the present invention, dielectrics or conductive substances for changing the electrical properties of the liquid crystal alignment film, such as the dielectric constant and conductivity, silane coupling agents for improving the adhesion between the liquid crystal alignment film and the substrate, cross-linking compounds for increasing the hardness and density of the film when the liquid crystal alignment film is formed, and imidization accelerators for effectively advancing the imidization by heating the polyimide precursor when the coating film is fired.
[0135] <Liquid crystal alignment film>
[0136] The liquid crystal alignment film of the present invention is a film obtained by applying the above-mentioned liquid crystal alignment agent to a substrate, drying it, and firing it. As a substrate for applying the liquid crystal alignment agent, if it is a substrate with high transparency, it is not particularly limited, and a glass substrate, a silicon nitride substrate, an acrylic substrate, a plastic substrate such as a polycarbonate substrate, etc. can be used. From the viewpoint of process simplification, it is preferred to use a substrate formed with an ITO electrode for driving liquid crystals. In addition, in a reflective liquid crystal display element, if only a single-sided substrate is used, even an opaque object such as a silicon wafer can be used, and the electrode at this time can also use a material that reflects light such as aluminum.
[0137] As a coating method of the liquid crystal aligning agent of this invention, a spin coating method, a printing method, an inkjet method, etc. are mentioned.
[0138] The drying and firing steps after applying the liquid crystal alignment agent can be performed at any temperature and time. In order to fully remove the organic solvent contained, the drying temperature is preferably 50 to 120°C and the drying time is preferably 1 to 10 minutes. In addition, the firing temperature is preferably 150 to 300°C and the firing time is preferably 5 to 120 minutes.
[0139] The thickness of the film after firing is not particularly limited, but if it is too thin, the reliability of the liquid crystal display element may be impaired, so it is preferably 5 to 300 nm, more preferably 10 to 120 nm.
[0140] As a method for photo-orientation treatment of a liquid crystal alignment film, there can be cited a method of irradiating the coating surface with radiation deflected in a certain direction, and then heating it at a temperature of 150 to 250°C as needed to impart liquid crystal orientation ability. As radiation, ultraviolet rays and visible light with a wavelength of 100 to 800nm can be used. Among them, ultraviolet rays with a wavelength of 100 to 400nm are preferred, and ultraviolet rays with a wavelength of 200 to 400nm are particularly preferred. In addition, in order to improve the orientation of the liquid crystal, the coating substrate can be irradiated with radiation while being heated at 50 to 250°C. The irradiation amount of the radiation is preferably 1 to 10000mJ / cm 2 , particularly preferably 100 to 5000 mJ / cm 2 The liquid crystal alignment film produced as described above can stably align liquid crystal molecules in a certain direction.
[0141] The higher the extinction ratio of polarized ultraviolet light, the more preferred it is because it can impart higher anisotropy. Specifically, the extinction ratio of linearly polarized ultraviolet light is preferably 10:1 or more, and more preferably 20:1 or more.
[0142] The film irradiated with the polarized radiation may then be subjected to a contact treatment with a solvent containing at least one selected from water and an organic solvent.
[0143] As the solvent used in the contact treatment, if it is a solvent that dissolves the decomposition product generated by light irradiation, it is not particularly limited. As a specific example, water, methanol, ethanol, 2-propanol, acetone, methyl ethyl ketone, 1-methoxy-2-propanol, 1-methoxy-2-propanol acetate, butyl cellosolve, ethyl lactate, methyl lactate, diacetone alcohol, 3-methoxy methyl propionate, 3-ethoxy ethyl propionate, propyl acetate, butyl acetate, cyclohexyl acetate, etc. can be listed. These solvents can be used in combination of two or more. From the viewpoint of versatility and safety, it is more preferably selected from at least one of the group consisting of water, 2-propanol, 1-methoxy-2-propanol and ethyl lactate. Particularly preferably water, 2-propanol or a mixed solvent of water and 2-propanol.
[0144] In the present invention, as the contact treatment between the film irradiated with polarized radiation and the solution containing an organic solvent, immersion treatment, spray treatment, etc. can be listed, and preferably the treatment in which the film is fully contacted with the liquid. Among them, it is preferred that the film is immersed in a solution containing an organic solvent for preferably 10 seconds to 1 hour, more preferably 1 to 30 minutes. The contact treatment can be carried out at room temperature or heated, but is preferably carried out at 10 to 80°C, more preferably 20 to 50°C. In addition, means such as ultrasound to improve contact can be implemented as needed.
[0145] After the contact treatment, in order to remove the organic solvent in the solution used, either or both of rinsing (washing) with a low boiling point solvent such as water, methanol, ethanol, 2-propanol, acetone, and methyl ethyl ketone or drying may be performed.
[0146] Furthermore, for the film that has been contact-treated with a solvent, in order to dry the solvent and reorient the molecular chains in the film, it can be heated at 150°C or above. The heating temperature is preferably 150 to 300°C. The higher the temperature, the more the reorientation of the molecular chains is promoted, but if the temperature is too high, it may be accompanied by the decomposition of the molecular chains. Therefore, the heating temperature is more preferably 180 to 250°C, and particularly preferably 200 to 230°C.
[0147] If the heating time is too short, the effect of reorientation of the molecular chains may not be obtained, while if it is too long, the molecular chains may be decomposed. Therefore, the heating time is preferably 10 seconds to 30 minutes, and more preferably 1 minute to 10 minutes.
[0148] <Liquid crystal display element>
[0149] The liquid crystal display element of the present invention is formed by obtaining a substrate having a liquid crystal aligning film formed from the liquid crystal aligning agent of the present invention, producing a liquid crystal cell by a known method, and forming an element using the cell.
[0150] As an example of a method for manufacturing a liquid crystal unit, a liquid crystal display element with a passive matrix structure is described below as an example. It should be noted that a liquid crystal display element with an active matrix structure in which a switching element such as a TFT (Thin Film Transistor) is provided in each pixel portion constituting the image display may also be used.
[0151] First, transparent glass substrates are prepared, a common electrode is provided on one substrate, and a segment electrode is provided on the other substrate. These electrodes can be formed into ITO electrodes, for example, and patterned in a manner that allows for the desired image to be represented. Next, an insulating film is provided on each substrate in a manner that covers the common electrode and the segment electrode. The insulating film can be, for example, a film containing SiO2-TiO2 formed by a sol-gel method.
[0152] Next, the liquid crystal alignment film of the present invention is formed on each substrate. Next, another substrate is overlapped on one substrate in a manner that the alignment film surfaces are mutually opposed, and the periphery is bonded with a sealing material. In order to control the substrate gap, it is usually preferred to mix a spacer into the sealing material. In addition, it is also preferred to pre-spread a spacer for controlling the substrate gap in the surface portion where the sealing material is not provided. In addition, an opening portion that can be filled with liquid crystal from the outside can usually be provided in a part of the sealing material.
[0153] Next, a liquid crystal material is injected into the space surrounded by the two substrates and the sealing material through the opening provided in the sealing material. Then, the opening is sealed with an adhesive. The injection can be performed by a vacuum injection method or by a method utilizing a capillary phenomenon in the atmosphere. Next, a polarizing plate is provided. Specifically, a pair of polarizing plates are attached to the surfaces of the two substrates on the opposite side to the liquid crystal layer. By going through the above steps, the liquid crystal display element of the present invention is obtained.
[0154] In the present invention, as the sealant, for example, a resin that is cured by ultraviolet irradiation or heating and has reactive groups such as epoxy, acryloyl, methacryloyl, hydroxyl, allyl, and acetyl is used. In particular, a curing resin system having reactive groups of both epoxy and (meth)acryloyl is preferably used.
[0155] In the above-mentioned sealant, in order to improve adhesion, moisture resistance, etc., an inorganic filler can be mixed. As the inorganic filler that can be used, it is not particularly limited, specifically, spherical silica, fused silica, crystalline silica, titanium oxide, titanium black, silicon carbide, silicon nitride, boron nitride, calcium carbonate, magnesium carbonate, barium sulfate, calcium sulfate, mica, talc, clay, aluminum oxide, magnesium oxide, zirconium oxide, aluminum hydroxide, calcium silicate, aluminum silicate, lithium aluminum silicate, zirconium silicate, barium titanate, glass fiber, carbon fiber, molybdenum disulfide, asbestos, etc. are preferably spherical silica, fused silica, crystalline silica, titanium oxide, titanium black, silicon nitride, boron nitride, calcium carbonate, barium sulfate, calcium sulfate, mica, talc, clay, aluminum oxide, aluminum hydroxide, calcium silicate, aluminum silicate, etc. The above-mentioned inorganic filler can be mixed with two or more and used.
[0156] Example
[0157] The present invention will be described in more detail below with reference to Examples, but the present invention is not limited thereto. It should be noted that the abbreviations of the compounds and the methods for measuring the properties are as follows.
[0158] NMP: N-methyl-2-pyrrolidone,
[0159] BCS: Butyl Cellosolve
[0160]
[0161] In the formula, Fmoc represents a 9-fluorenylmethoxycarbonyl group, and Boc represents a tert-butoxycarbonyl group.
[0162] [ 1 H NMR]
[0163] Equipment: Fourier transform superconducting nuclear magnetic resonance device (FT-NMR) INOVA-400 (Varian) 400 MHz
[0164] Solvent: Deuterated dimethyl sulfoxide (DMSO-d6)
[0165] Standard substance: Tetramethylsilane (TMS)
[0166] Cumulative times: 8 or 32
[0167] [Viscosity]
[0168] The viscosity of the polyimide and polyamic acid solutions was measured using an E-type viscometer (VE-22H manufactured by Toki Sangyo Co., Ltd.) at a sample volume of 1.1 mL, a cone rotor TE-1 (1°34', R24), and a temperature of 25°C.
[0169] [Fabrication of Liquid Crystal Cell]
[0170] A liquid crystal cell having a structure of an FFS mode liquid crystal display element was produced.
[0171] First, prepare a substrate with electrodes. The substrate is a glass plate with a size of 30 mm × 50 mm and a thickness of 0.7 mm. An ITO electrode with a solid pattern constituting a counter electrode is formed on the substrate as the first layer. On the counter electrode of the first layer, a SiN (silicon nitride) film formed by a CVD method is formed as the second layer. The thickness of the SiN film of the second layer is 500 nm, and it functions as an interlayer insulating film. On the second layer of SiN film, a comb-shaped pixel electrode formed by patterning the ITO film is arranged as the third layer to form two types of pixels, the first pixel and the second pixel. The size of each pixel is 10 mm in length and about 5 mm in width. At this time, the counter electrode of the first layer and the pixel electrode of the third layer are electrically insulated by the action of the SiN film of the second layer.
[0172] The pixel electrode of the third layer has a comb-like shape composed of a plurality of arranged electrode elements in the shape of a "く" character with a central portion bent at an inner angle of 160°. The width of each electrode element in the width direction is 3μm, and the interval between the electrode elements is 6μm. The pixel electrode forming each pixel is composed of a plurality of arranged electrode elements in the shape of a "く" character with a central portion bent, so the shape of each pixel is not a rectangular shape, but has a shape similar to a "く" character with a central portion bent like the electrode elements. And each pixel is divided into upper and lower parts by the central bent portion as a boundary, with a first area on the upper side of the bent portion and a second area on the lower side.
[0173] The obtained liquid crystal alignment agent was then filtered with a filter having a pore size of 1.0 μm, and then applied to the prepared substrate with electrodes and a glass substrate with a columnar spacer having a height of 4 μm and an ITO film formed on the back by spin coating. After drying on a hot plate at 80°C for 2 minutes, it was sintered in a hot air circulation oven at 230°C for 30 minutes to form a coating film with a thickness of 100 nm. The coating surface was heated at 500 mJ / cm 2 Irradiate polarized ultraviolet rays to carry out orientation treatment to obtain a substrate with a liquid crystal orientation film. It should be noted that the liquid crystal orientation film formed on the above-mentioned substrate with electrodes is oriented in a manner that the direction that divides the inner angle of the pixel bending part into equal parts is orthogonal to the orientation direction of the liquid crystal, and the liquid crystal orientation film formed on the second glass substrate is oriented in a manner that the orientation direction of the liquid crystal on the first substrate is consistent with the orientation direction of the liquid crystal on the second substrate when the liquid crystal unit is made. The above-mentioned two substrates are taken as a group, and a sealant is printed on the substrate. After bonding another substrate in a manner that the orientation direction of the liquid crystal orientation film surface relative to each other forms 0°, the sealant is cured to make an empty unit. Liquid crystal MLC-3019 (manufactured by Merck Ltd.) is injected into the empty unit by a reduced pressure injection method, and the injection port is sealed to obtain an FFS-driven liquid crystal unit. The obtained liquid crystal unit is then heated at 110°C for 1 hour, left overnight, and used for residual image evaluation.
[0174] [Evaluation of afterimage caused by long-term AC drive]
[0175] Using the above liquid crystal cell, an AC voltage of ±5 V was applied at a frequency of 30 Hz for 120 hours in a constant temperature environment of 60° C. Then, the pixel electrode and the counter electrode of the liquid crystal cell were short-circuited and left at room temperature for one day.
[0176] After placement, the liquid crystal unit is set between two polarizing plates arranged in a manner that the polarization axes are orthogonal, the backlight source is pre-lit in a state where no voltage is applied, and the configuration angle of the liquid crystal unit is adjusted in a manner that the brightness of the transmitted light is minimized. Then, the rotation angle when the liquid crystal unit is rotated from the darkest angle of the second area of the first pixel to the darkest angle of the first area is calculated as angle Δ. Similarly, for the second pixel, the second area is compared with the first area to calculate the same angle Δ. Then, the average value of the angle Δ values of the first pixel and the second pixel is calculated as the angle Δ of the liquid crystal unit.
[0177] The angle Δ of the liquid crystal cell obtained above was evaluated as “×” when it was 0.15° or more, “△” when it was less than 0.15° and 0.1° or more, and “0” when it was less than 0.1°.
[0178] (Synthesis Example 1: Synthesis of DA-5)
[0179] DA-5 was synthesized according to the following steps.
[0180]
[0181] Synthesis of compound [1]
[0182] Ethylene glycol ditoluene sulfonate (40.6 g, 110 mmol), 4-hydroxy-4'-nitrobiphenyl (49.5 g), and potassium carbonate (37.8 g) were added to dimethylformamide (500 g) and stirred at 80°C for 23 hours. After cooling to room temperature, the mixture was poured into pure water (1000 g) and stirred to precipitate crystals. The crystals were filtered, and the filtrate was slurry-washed with methanol (500 g), filtered, and then dried to obtain a crude product (47.6 g). Dimethylformamide (333 g) was added to the crude product, heated at 100°C to dissolve, and then methanol (333 g) was added and cooled to precipitate crystals. After filtering, the filtrate was dried to obtain compound [1] (yield: 40.2 g, yield: 80%, yellow crystals).
[0183] 1H-NMR (400MHz, DMSO-d6, δppm): 8.28 (d, 4H, J = 9.2Hz), 7.95 (d, 4H, J = 9.2Hz), 7.80 (d, 4H, J = 9.2Hz), 7.17 (d, 4H, J = 9.2Hz), 4.44 (s, 4H).
[0184] Synthesis of compound [DA-5]
[0185] Compound [1] (40.2 g) and 5% palladium carbon (4.0 g) were added to dimethylformamide (800 g), and stirred at 60°C for 19 hours under a hydrogen atmosphere. After nitrogen substitution, dimethylformamide (680 g) was added, and the diamine was heated and dissolved at 130°C. The catalyst was hot filtered, and a portion of the filtrate was concentrated to a content of 813 g. Dimethylformamide (60 g) was added, and after dissolving at 120°C, methanol (838 g) was added and cooled to precipitate crystals. After filtering, the filtrate was dried to obtain compound [DA-5] (yield: 33.6 g, yield: 96%, yellow earth-colored crystals).
[0186] 1H-NMR (400MHz, DMSO-d6, δppm): 7.46 (d, 4H, J = 8.8Hz), 7.29 (d, 4H, J = 8.8Hz), 7.00 (d, 4H, J = 8.8Hz), 6.61 (d, 4H, J = 8.8Hz), 5.13 (br, 4H), 4.32 (s, 4H).
[0187] (Synthesis example 2)
[0188] DA-1 1.30 g (12.0 mmol), DA-2 2.93 g (12.0 mmol), and DA-6 2.05 g (6.00 mmol) were weighed in a 100 mL four-necked flask equipped with a stirrer and a nitrogen inlet tube, and then 77 g of NMP was added, and stirred and dissolved while nitrogen was supplied. DAH-1 6.19 g (27.6 mmol) was added while stirring the diamine solution, and NMP was further added so that the solid content concentration was 12% by mass, and stirred at 40° C. for 12 hours to obtain a solution of polyamic acid (PAA-1) (viscosity: 340 mPa·s).
[0189] (Synthesis example 3)
[0190] DA-1 1.17 g (10.8 mmol), DA-3 3.46 g (10.8 mmol), and DA-6 1.84 g (5.39 mmol) were weighed in a 100 mL four-necked flask equipped with a stirrer and a nitrogen inlet tube, and then 75 g of NMP was added, and stirred and dissolved while nitrogen was supplied. DAH-1 5.57 g (24.8 mmol) was added while stirring the diamine solution, and NMP was further added so that the solid content concentration was 12% by mass, and stirred at 40° C. for 12 hours to obtain a solution of polyamic acid (PAA-2) (viscosity: 340 mPa·s).
[0191] (Synthesis Example 4)
[0192] DA-1 1.17 g (10.8 mmol), DA-4 4.43 g (10.8 mmol), and DA-6 1.84 g (5.39 mmol) were weighed in a 200 mL four-necked flask equipped with a stirrer and a nitrogen inlet tube, and then 83 g of NMP was added, and stirred and dissolved while nitrogen was supplied. DAH-1 5.75 g (25.7 mmol) was added while stirring the diamine solution, and NMP was further added so that the solid content concentration was 12% by mass, and stirred at 40° C. for 12 hours to obtain a solution of polyamic acid (PAA-3) (viscosity: 360 mPa·s).
[0193] (Synthesis Example 5)
[0194] DA-1 0.56 g (5.18 mmol), DA-5 2.06 g (5.20 mmol), and DA-6 0.89 g (2.61 mmol) were weighed in a 100 mL four-necked flask equipped with a stirrer and a nitrogen inlet tube, and then 39 g of NMP was added, and stirred and dissolved while nitrogen was supplied. DAH-1 2.68 g (12.0 mmol) was added to the diamine solution while stirring, and NMP was further added so that the solid content concentration was 12% by mass, and stirred at 40° C. for 12 hours to obtain a solution of polyamic acid (PAA-4) (viscosity: 215 mPa·s).
[0195] (Synthesis Example 6)
[0196] DA-7 3.83 g (19.2 mmol) and DA-8 1.43 g (4.79 mmol) were weighed in a 100 mL four-necked flask equipped with a stirrer and a nitrogen inlet tube, and then NMP 78 g was added, and stirred and dissolved while nitrogen was supplied. DAH-2 6.56 g (22.2 mmol) was added to the diamine solution while stirring, and NMP was further added so that the solid content concentration was 12% by mass, and stirred at 70° C. for 20 hours to obtain a polyamic acid (PAA-5) solution (viscosity: 420 mPa·s).
[0197] (Comparative Example 1)
[0198] 6.25 g of the polyamic acid solution (PAA-1) obtained in Synthesis Example 2 was weighed into a 50 mL conical flask containing a stirrer, and then 3.50 g of NMP and 4.5 g of BCS were added, and stirred overnight with a magnetic stirrer to obtain a liquid crystal aligning agent (AL-1).
[0199] (Comparative Example 2)
[0200] 6.25 g of the polyamic acid solution (PAA-2) obtained in Synthesis Example 3 was weighed into a 50 mL conical flask containing a stirrer, and then 3.50 g of NMP and 4.5 g of BCS were added, and stirred overnight with a magnetic stirrer to obtain a liquid crystal aligning agent (AL-2).
[0201] (Comparative Example 3)
[0202] 6.25 g of the polyamic acid solution (PAA-3) obtained in Synthesis Example 4 was weighed into a 50 mL conical flask containing a stirrer, and then 3.50 g of NMP and 4.5 g of BCS were added, and stirred overnight with a magnetic stirrer to obtain a liquid crystal aligning agent (AL-3).
[0203] (Example 1)
[0204] 6.25 g of the polyamic acid solution (PAA-4) obtained in Synthesis Example 5 was weighed into a 50 mL conical flask containing a stirrer, and then 3.50 g of NMP and 4.5 g of BCS were added, and stirred overnight with a magnetic stirrer to obtain a liquid crystal aligning agent (AL-4).
[0205] (Example 2)
[0206] 2.50 g of the polyamic acid solution (PAA-4) obtained in Synthesis Example 5 and 3.75 g of the polyamic acid solution (PAA-5) obtained in Synthesis Example 6 were measured in a 50 mL conical flask with a stirrer. 3.50 g of NMP and 4.50 g of BCS were added, 0.75 g of a 10% NMP solution of AD-1, and 0.113 g of AD-2 were added, and stirred overnight with a magnetic stirrer to obtain a liquid crystal aligning agent (AL-5). AL-5 was stored at -20 ° C to confirm its stability during frozen storage. It was confirmed that there was no precipitation after 1 month of frozen storage, and the filterability was also good.
[0207] (Comparative Example 4)
[0208] The liquid crystal alignment agent (AL-1) obtained in Comparative Example 1 was evaluated for residual images due to long-term AC driving as described above. That is, a liquid crystal unit having a structure of an FFS mode liquid crystal display element was prepared as described above using the liquid crystal alignment agent (AL-1), and the residual images due to long-term AC driving were evaluated for the FFS driven liquid crystal unit. As a result, the value of the angle Δ of the liquid crystal unit after long-term AC driving was 0.16 degrees.
[0209] (Comparative Example 5)
[0210] A FFS-driven liquid crystal cell was prepared in the same manner as in Comparative Example 4 except that the liquid crystal alignment agent (AL-2) obtained in Comparative Example 2 was used. The FFS-driven liquid crystal cell was subjected to an afterimage evaluation due to long-term AC driving. The value of the angle Δ of the liquid crystal cell after long-term AC driving was 0.11 degrees.
[0211] (Comparative Example 6)
[0212] A FFS-driven liquid crystal cell was prepared in the same manner as in Comparative Example 4 except that the liquid crystal alignment agent (AL-3) obtained in Comparative Example 3 was used. The FFS-driven liquid crystal cell was subjected to an afterimage evaluation due to long-term AC driving. The value of the angle Δ of the liquid crystal cell after long-term AC driving was 0.17 degrees.
[0213] (Example 3)
[0214] A FFS-driven liquid crystal cell was prepared in the same manner as in Comparative Example 4 except that the liquid crystal alignment agent (AL-4) obtained in Example 1 was used. The FFS-driven liquid crystal cell was subjected to an afterimage evaluation due to long-term AC driving. The value of the angle Δ of the liquid crystal cell after long-term AC driving was 0.05 degrees.
[0215] (Example 4)
[0216] The polymer 2-component mixed liquid crystal aligning agent (AL-5) obtained in Example 2 was filtered with a filter having a pore size of 1.0 μm, and then spin-coated on a glass substrate with a transparent electrode and dried on a hot plate at a temperature of 80°C for 2 minutes. Then, it was calcined in an IR oven at a temperature of 230°C for 30 minutes to obtain an imidized film with a film thickness of 100 nm. The state of the calcined film was confirmed, and it was confirmed that there was no unevenness or difficulty in brushing, and the film could be formed uniformly.
[0217] Table 1 shows the results of the residual image evaluation by long-term cross-linking driving of the liquid crystal aligning agents of Comparative Examples 4 to 6 and Example 3 in a summary.
[0218] [Table 1]
[0219] Liquid crystal alignment agent Polymer composition Afterimage caused by long-term AC drive Comparative Example 4 AL-1 PAA-1 × Comparative Example 5 AL-2 PAA-2 △ Comparative Example 6 AL-3 PAA-3 × Example 3 AL-4 PAA-4 ○
[0220] It should be noted that the entire contents of the specification, patent claims, and abstract of Japanese Patent Application No. 2018-209060 filed on November 6, 2018 are incorporated herein by reference as a public introduction to the specification of the present invention.
Claims
1. A liquid crystal aligning agent comprising at least one polymer selected from the group consisting of a polyimide precursor having a structure represented by the following formula (1) in the main chain and an imidized polymer of the polyimide precursor, -B1-R1-A-R2-B2- (1) In formula (1), R1 and R2 are each independently a single bond, -O-, -S-, or -NR 12 -, R 12 is a hydrogen atom or a methyl group, A is an alkylene group having a carbon chain of 2, B1 and B2 have the same structure and are a divalent organic group selected from the following structures, The polyimide precursor is obtained by subjecting a diamine component and a tetracarboxylic acid component to a polymerization reaction, wherein the diamine component includes a diamine having amino groups bonded to both ends of the structure of the formula (1). The polyimide precursor is a polymer containing a structural unit of the following formula (2), In formula (2), X1 is at least one selected from the group consisting of structures represented by the following formula (X1-1) and formula (X1-2), Y1 is a divalent organic group represented by the above formula (1), R3 is a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, Z1 and Z2 are each independently a hydrogen atom, or an alkyl group having 1 to 10 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, or an alkynyl group having 2 to 10 carbon atoms which may have a substituent, The polyimide precursor has 20 to 100 mol% of the structural unit represented by the formula (2) based on all structural units.
2. The liquid crystal alignment agent according to claim 1, wherein The diamine component contains at least one diamine selected from the following: R 12 The same as the above formula (1).
3. The liquid crystal alignment agent according to claim 2, wherein: The diamine component contains at least one diamine selected from the following: R 12 The same as the above formula (1).
4. The liquid crystal aligning agent according to claim 1 or 2, wherein In the formula (2), X1 is the following formula (X1-2), 5. The liquid crystal aligning agent according to claim 1 or 2, wherein In the above formula (2), R3 is a hydrogen atom or a methyl group, and Z1 and Z2 are a hydrogen atom or an alkyl group having 1 to 5 carbon atoms which may have a substituent.
6. The liquid crystal aligning agent according to claim 1 or 2, wherein: The polyimide precursor further contains a structural unit of the following formula (3), In the formula (3), R3, Z1 and Z2 are defined the same as in the above formula (2), X2 is a tetravalent organic group, and Y2 is a divalent organic group.
7. The liquid crystal aligning agent according to claim 1 or 2, wherein: The concentration of the polymer is 1 mass % or more and 10 mass % or less with respect to the total amount of the liquid crystal aligning agent. 8 . A liquid crystal aligning film obtained by applying the liquid crystal aligning agent according to claim 1 and irradiating a film obtained by baking with polarized ultraviolet rays. 9 . A liquid crystal display element comprising the liquid crystal aligning film according to claim 8 .
Citation Information
Patent Citations
Method for orienting liquid crystal
JP1997297313A
Liquid crystal aligning agent, liquid crystal alignment film and liquid crystal display element
CN107615145A
Liquid crystal alignment agent, liquid crystal alignment film, liquid crystal display device, retardation film and method for manufacturing the same, polymer, and compound
JP2016006473A
Liquid crystal aligning agent, liquid crystal alignment film, method for producing same, liquid crystal element and polymer
WO2018159284A1